The impacts of rural outmigration on women’s empowerment: Evidence from Nepal, Senegal, and Tajikistan - Slavchevska, Vanya; Hillesland, Marya; Mane, Erdgin; Doss, Cheryl (International Food Policy Research Institute, 2021)
Using primary survey data collected in Tajikistan, Nepal and Senegal, three countries with high male outmigration rates, this study analyzes the impacts of migration on the empowerment of women who remain in rural areas. The study uses indicators from the Abbreviate Women’s Empowerment in Agriculture Index (A-WEAI) to measure women’s empowerment in five domains (decision-making autonomy around agricultural production, resources, control over income, group membership and workload) and instrumental variable approaches to address the endogeneity between the migration of a family member and women’s empowerment. It finds that male outmigration leads to women’s empowerment in agriculture in some domains and disempowerment in others. In Tajikistan, where women start with low levels of empowerment, women in households with a migrant are more likely to be involved in decisions in productive activities on the household farm, control income, own assets and achieve workload balance than women in non-migrant households. In Nepal and Senegal, women start at higher levels of empowerment and we see fewer differences in their empowerment based on whether they live in a migrant-sending household. The impacts of migration on empowerment depend on the context, whether the household receives remittances or owns land, and women’s position within the household.